2003
DOI: 10.1063/1.1542674
|View full text |Cite
|
Sign up to set email alerts
|

Flux pinning enhancement in ferromagnetic and superconducting thin-film multilayers

Abstract: Flux pinning in high-temperature superconductors such as YBa 2 Cu 3 O 7Ϫx ͑YBCO͒ in the past has been accomplished by pinning the vortex cores. We demonstrate magnetic-domain-induced flux pinning of the magnetic flux of vortices in a ferromagnet-superconductor bilayer consisting of CoPt grown on YBCO, where the ferromagnet has uniaxial perpendicular magnetic anisotropy and a random domain structure. We observe an improvement of the critical current due to magnetic pinning at temperatures close to the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…(693) Several experimental studies confirmed that this type of pinning enhancement occurs, both in multilayers and in the FM/SC bilayers (FSBs) [2][3][4][5][6]. In particular, we have studied the FSBs consisting of Nb film deposited on the top of Co/Pt multilayer, and we found that the pinning is enhanced exclusively in the final stages of the magnetic reversal process of the FM layer.…”
Section: Introductionmentioning
confidence: 79%
“…(693) Several experimental studies confirmed that this type of pinning enhancement occurs, both in multilayers and in the FM/SC bilayers (FSBs) [2][3][4][5][6]. In particular, we have studied the FSBs consisting of Nb film deposited on the top of Co/Pt multilayer, and we found that the pinning is enhanced exclusively in the final stages of the magnetic reversal process of the FM layer.…”
Section: Introductionmentioning
confidence: 79%
“…The interaction between vortices and pinning centers has been studied extensively for decades, focused mainly on the so-called vortex core pinning (caused by the local suppression of the superconducting order parameter) [1,2]. Less explored is the interplay between vortices and magnetic media, which could offer pinning forces superior to those from core pinning [3][4][5][6]. A common difficulty of studying magnetic pinning is the inability of separating the magnetic and core contributions.…”
mentioning
confidence: 99%
“…The two macroscopic quantum states in S and F layers influence each other via the penetration of superconducting (proximity effect) 2 and ferromagnetic (inverse proximity effect) [3][4][5] order through their common interface. In presence of strong enough magnetic fields, the vortices in the S-layer can couple with the magnetic domains of the F-layer leading to interesting effects of domain wall pinning of the vortices and vice-a-versa, and domain wall superconductivity [6][7][8][9][10] . Most of such studies have been carried out with ferromagnetic component consisting of 3d transition metals like Fe, Co and Ni, and their alloys.…”
mentioning
confidence: 99%